PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2021) - Linuwih, Devania Rizky; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2024)
The aim of this research is to examine the influence of Good Corporate Governance on Company Financial Performance. The phenomenon was a drastic decline in financial performance on multiindustry companies compared with others in 2020, which led to several industrial-sector companies suspend their share and decline.Good Corporate Governance in this research is proxied by the board accountability, transparency and disclosure, and audit committee. The company's financial performance in this study was measured using ROE and Tobin's q. The sample used is a multi-industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2019-2021. The sampling method used purposive sampling with several criteria, so that a sample of 29 companies was obtained. The type of data used is secondary data obtained on the website www.idx.co.id and the official research sample company website.The results of statistical tests conclude that the board accountability would have a significant impact on their financial performance using both roe and tobin's q, while transparency and disclosure, and the audit committee would have no effect on the company's financial performance.